Escalating Complexity in Regional Conflicts: Connecting Geopolitics to Individual Pathways to Terrorism in Mali. Issue 3 (3rd July 2018) - Dal Santo, Elena; van der Heide, Elizabeth Johanna
ABSTRACT: In 2012, Northern Mali was the theater of a Tuareg rebellion that has rapidly transformed into a much more complex armed conflict. The current situation is affected by various factors, such as the influence of regional geopolitical dynamics, the increasing presence of terrorist, pro-government or secessionist paramilitary groups, and the synergies between terrorism and organized crime. Through analyzing existing literature and field research, this article addresses the question: what factors play a role in the current conflict in Mali? Conflict evolution will be placed in the broader historical and geopolitical framework to then assess individual push and pull factors.